Stability of Output and Employment in Islamic Macroeconomic Models - Erisa Sandra Angela; Mohamad Anton Athoillah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2026)
This study addresses the persistent challenge of global financial instability and the inability of conventional macroeconomic frameworks to resolve socio-economic disparities, such as high unemployment and poverty in Indonesia. The primary objective is to qualitatively analyze the mechanisms through which Islamic macroeconomic models achieve stability in output and employment, focusing on the synergy between risk-sharing financial structures and social justice institutions. The research utilizes a qualitative approach with a naturalistic descriptive method, where the researcher acts as the key instrument to explore emic perspectives. Data collection is conducted through triangulation of in-depth documentation studies (library research), drawing from primary classical fiqh muamalah texts and secondary contemporary academic journals and policy reports. The main findings reveal three core themes: (1) the synchronization of the real and financial sectors through risk-sharing mechanisms (Mudharabah and Musharakah); (2) the function of Zakat as an automatic stabilizer for aggregate demand by penalizing idle capital; and (3) an ethical commitment to full employment, viewing labor as a spiritual obligation (ibadah. These findings contribute to a holistic understanding of economic resilience driven by the internalization of falah (holistic welfare). Theoretically, this research implies the need to redefine stability parameters to include distributive justice . Practically, it suggests strengthening coordination between Indonesian monetary authorities and social finance institutions like BAZNAS . Future research should consider empirical calibrations using real-time post-pandemic data.